Methods Of Organizing Sports Training (Diversity Research: Journal of Analysis and Trends, 2023)
In the process of sports training, all these methods are used in various combinations. Each method is not used in a standard way, but is constantly adapted to the specific requirements due to the characteristics of sports training. When choosing methods, one should ensure that they strictly correspond to the tasks set, general didactic, as well as special principles of sports training, age and gender characteristics, their qualifications and preparedness